PSI-10 Effects of a Moderate and Aggressive Implant Strategy on the Rumen Microbial Community in Steers. (30th November 2020) - Henniger, Madison T; Wells, Jim E; Hales, Kristin E; Lindholm-Perry, Amanda K; Freetly, Harvey C; Kuehn, Larry A; Schneider, Liesel G; McLean, Kyle J; Clemmons, Brooke A; Myer, Phillip R
Abstract: The effects of growth-promoting implant strategies have been well-defined in research for their ability to impact growth performance in beef cattle. Production-relevant microbiomes in the rumen have also been associated with growth traits. However, the role of implant strategies on the rumen microbiome is not understood. The objective was to determine if varying doses of implant hormones cause gain-associated ruminal microbial community shifts. To assess this, a completely randomized design was used and 336 fall-born steers from the germplasm evaluation population between 450–470 days of age at the U.S. Meat Animal Research Center (Clay Center, NE) were divided into two treatment groups: 1) a moderate implant strategy of Revalor-IS (80 mg trenbolone acetate, 16 mg estradiol) followed by Revalor-S (120 mg trenbolone acetate, 24 mg estradiol) and 2) an aggressive implant strategy of Revalor-IS followed by Revalor-200 (200 mg trenbolone acetate, 20 mg estradiol). Steers were fed the same diet (57.0% dry-rolled corn, 30% wet distiller's grains with solubles, 8.0% alfalfa hay, 4.25% supplement, and 0.75% urea, DM basis). Body weights were collected once per month with initial weights of 439.8 ± 43.1 kg. After implants were administered for 84 days, rumen content was collected via orogastric tubing. Samples were sequenced targeting bacterial V1-V3 16S rRNA gene regions, V3-V4 for archaea, and partial 18S rRNA gene of protozoa. Sequences were processed in R utilizing Phyloseq and analyzed with DESeq2 to test differential abundances. Production data between implant strategies were analyzed using a mixed model ANOVA (SASv9.4, Cary, NC). Alpha- and beta-diversity between strategies did not differ for bacteria, archaea, or protozoa (P > 0.05). Average daily gain was different (P = 0.01; 1.72 vs 1.66 ± 0.02 kg, aggressive vs moderate, respectively); however, large microbial community shifts were not associated implant strategy. USDA is an equal opportunity provider and employer.